Biomolecular interactions at the surfaces in aqueous and non-aqueous solutions - Aryafard, Meysam (Jihočeská univerzita, 2023)
Knowledge of interactions in solvents helps to choose a good solvent, save time and costs to find a solution, and improve the efficiency of reactions. Understanding adding a co-solvent to another solvent is important as well because of their needs in several biological and chemical applications. This becomes more difficult when one of the solvents is an ionic solvent (DESs, ILs) which consists of several components. MD simulation is a powerful technique to understand the physical nature of some interactions at the molecular levels in complex media. As well, solvatochromic parameters present useful knowledge of interactions by experimental methods. Three famous DESs named reline, ethaline, and glyceline were chosen to measure their interactions with green co-solvents (water, PEG 400). Also, amino acid ionic liquids were studied as well. This research was a combined experimental and theoretical study to see the agreement between the experimental and computational results. Solvent-solvent, solute-solvent, solvatochromic parameters, preferential solvation model, and ions solvations were investigated in the binary mixtures of DESs/ILs with organic solvents. Moreover, our knowledge resulted in synthesizing novel ILs and DESs with good benefits in several applications and some of usages were investigated.
Biomolecular interactions at the surfaces in aqueous and non-aqueous solutions
Keywords: Deep eutectic solvents; ionic liquids; MD simulation; binary mixtures; preferential solvation parameters; solvatochromic parameters; solvation structures.; Deep eutectic solvents; ionic liquids; MD simulation; binary mixtures; preferential solvation parameters; solvatochromic parameters; solvation structures.